Effect of non-genetic factors on colostrum and production traits of Phule TriveDi (triple crossbred) cattle - NAGAWADE, P P; JAGTAP, D Z; KAMBLE, S S (The Indian Journal of Animal Sciences, 2011)
Records (588) of 144 Phule Triveni (triple crossbred) cattle for colostrum and production traits i.e. colostrum yield at 1st to 4th day (CYA 1,2,3 and 4) and colostrum yield up to 4th day (CYU 4), production traits such as lactational milk yield (LMY), lactation length (LL), daily milk yield of lactation length (DMY/LL) and milk yield of 300 days (MY300) for period of 26 years (1977-2003) were collecte from Research-cum-Development Project on Cattle, Mahatma Phule Krishi Vidyapeeth, Rahuri. Influence of parity, period of calving (POC) and season of calving (SOC) were assessed on traits under study. Parity and period of calving had highly significant effect on all traits except LL. milk Whereas, SOC had nonsignificant effect on all traits. Â